SOSIALISASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SISWA-SISWI SD NEGERI 34 KENDARI - Jabbar, Asriullah; Nasrudin, Nasrudin; Muliadi, Rahmat; Zahra, Nurul; Irmawati, Irmawati; Setiawan, Laode Wawan; Apriliani, Mumut; Rosmeydar, Rosmeydar; Mubarak, Mubarak; Y, Muhammad Ilyas; Juwita, Diana (MAJU : Indonesian Journal of Community Empowerment, 2025)
The importance of raising awareness of PHBS in school-age children because schools have a strategic role and position in health education and promotion efforts. PHBS indicators used include washing hands with clean water and consuming healthy snacks. The implementation of community service activities carried out at SD Negeri 34 Kendari,  in class IV was carried out in several stages: 1. Preparation 2. Implementation 3. Evaluation This socialization can increase the knowledge of students of SD Negeri 34 Kendari about how to live a clean and healthy life in the elementary school environment as evidenced by getting good and enthusiastic responses from students when answering questions and practicing the correct way to wash their hands.